About scientific schools in the Nikolaev Astronomical Observatory in the fields of positional astronomy and astronomical instrumentation - Petrov, G.M.; Pinigin, G.I.; Shulga, A.V. (Кинематика и физика небесных тел, 2005)
The Nikolaev Astronomical Observatory (NAO) was founded in 1821. In the initial “naval” time of its growth the observatory also carried out some works of an astronomical character. Later on, and especially in the last decades there have been finally formed two main directions of scientific activity at the NAO, as position determination for celestial bodies and astronomical instrumentation.